Signifikasi Lirik Lagu “Asmalibrasi” Karya Soegi Bornean dalam Perspektif Semiotika Roland Barthes - Muhammad Irfan Maulana; Hisyam Zaini; Ridwan Ridwan (FKIP, Universitas Palangka Raya, 2024)
The song Asmalibrasi is one of the songs from Soegi Bornean. The song's lyrics use a lot of diction that is rarely used in everyday language. There is an assumption that terminology and the song flow become a sign and carry a particular message, so further study is needed. Among several theories related to symbols and meanings, Roland Barthes' theory of Semiotics which has the concept of connotative meaning and myth, is considered appropriate to be used as an analytical knife in this study. It is because there is a meaning in the second stage that can help reveal a connotative message and its myth. This research looks for the sign system's shape and the myths that appear in the song. Analysis of this study revealed that the music expresses the phenomenon of love and affection that lovers are experiencing. This song is considered revolutionary because some expressions describe the meanings in the form of the value of kindness and happiness in a romantic relationship, represented by beautiful lyrics. Some of the connotative meanings in the data indicate the existence of one myth that influences the song's narrative and becomes the main ideology, namely loyalty.